Microscopic Detection of Entamoeba gingivalis and Trichomonas tenax in Saliva and Subgingival Plaque Across Periodontal Health, Gingivitis, and Periodontitis: A Cross-Sectional Study - Bilge Meraci Yildiran; Mücahit Çakmak; Nuray Ercan (Journal of Clinical Medicine, 2026)
Background/Objectives: The oral protozoa Entamoeba gingivalis (E. gingivalis) and Trichomonas tenax (T. tenax) have been implicated in periodontal disease, yet their relationship to clinical periodontal status remains unresolved. This study examined their detection frequency by light microscopy across periodontally healthy, gingivitis, and periodontitis groups, and its association with clinical periodontal parameters. Methods: In this single-center, cross-sectional study, 120 adults were allocated to three equal groups (n = 40 each): periodontally healthy, gingivitis, and periodontitis. From each participant, subgingival plaque was collected from the deepest periodontal pocket or sulcus of every quadrant, together with unstimulated saliva. Each specimen was examined as an unstained saline wet mount and with a Lugol iodine preparation under light microscopy. Data were analyzed using Chi-square, Kruskal–Wallis, and Mann–Whitney U tests. Results: E. gingivalis was detected in 20/120 participants: 7.5% in periodontally healthy, 20.0% in gingivitis, and 22.5% in periodontitis, a difference that did not reach statistical significance (p = 0.156). T. tenax was not detected in any participant (0/120). Positive participants had greater full-mouth probing pocket depth than negative participants (median 1.89 vs. 1.59 mm; p = 0.025). Conclusions: On microscopic examination of this sample, E. gingivalis detection did not differ significantly between periodontal groups, whereas T. tenax was not encountered. Among the clinical parameters examined, positivity for E. gingivalis was associated with probing pocket depth, consistent with the organism occupying the deep subgingival niche. Longitudinal molecular studies in larger, multicenter samples are warranted.